Formulation of benzoxaborole drugs in PLLA: from materials preparation to in vitro release kinetics and cellular assays. Issue 2 (9th December 2015) - Sene, Saad; McLane, Joshua; Schaub, Nicholas; Bégu, Sylvie; Hubert Mutin, P.; Ligon, Lee; Gilbert, Ryan J.; Laurencin, Danielle
Abstract : A complete investigation on the incorporation of simple benzoxaboroles into PLLA-based films was carried out. Abstract : Benzoxaboroles are a family of organoboron molecules, which have been finding over the past few years an increasing number of biological applications, notably for the design of new drugs. Given that these molecules are still relatively new in the biomedical context, very few investigations regarding their formulation have been reported to date. Here, a complete study on the formulation of benzoxaboroles in a biopolymer, poly-l -lactic acid (PLLA), is reported. The incorporation of two small benzoxaboroles, namely the simplest benzoxaborole molecule (BBzx) and the antifungal drug tavaborole (AN2690), inside PLLA films was investigated. Different variations in the film composition and texture were looked into, by performing a heat-treatment on the PLLA films, or by preparing PLLA–PEO (polyethylene oxide) blends or PLLA–LDH (layered double hydroxide) composites. In each case, the impact of these changes in formulation on the local environment of the benzoxaboroles in the material (as determined by multinuclear solid state NMR), and on the kinetics of release in physiological media were analyzed, showing that a variety of release profiles could be achieved. Finally, cellular assays were carried out looking at the migration of MDA-MB-231 cancer cells. These tests revealed for the first time that benzoxaboroles like AN2690 and BBzx inhibited the migration of these cells. Moreover, the molecules incorporated in the films were found to remain active, and their effect on cancer cells was directly related to the release kinetics from the films. All in all, PLLA-based materials appear as highly versatile and attractive matrices for formulating benzoxaborole-based drugs.